Averaging of multivalued differential equations - G. Grammel (International Journal of Mathematics and Mathematical Sciences)
Nonlinear multivalued differential equations with slow and fast subsystems are considered. Under transitivity conditions on the fast subsystem, the slow subsystem can be approximated by an averaged multivalued differential equation. The approximation in the Hausdorff sense is of order O(ϵ1/3) as ϵ→0.